2018
DOI: 10.1038/s41598-018-35304-8
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome analysis provides insight into prickle development and its link to defense and secondary metabolism in Solanum viarum Dunal

Abstract: Prickles are epidermal outgrowth found on the aerial surface of several terrestrial plants. Microscopic studies on prickles of S. viarum Dunal indicated a crucial role of glandular trichomes (GTs) in their development. A spontaneously obtained prickleless mutant showed normal epidermal GTs, but its downstream developmental process to prickle was perturbed. Thus, prickleless mutant offers an ideal opportunity to unveil molecular regulators working downstream to GTs in the prickle formation. Differential transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…We identified two different types of prickles in our population: it appears that GP and NGP originate from glandular and non-glandular structures, respectively. This conclusion is different from previous studies in rose, which reported that prickles were extensions or modifications of glandular trichomes (Kellogg et al 2011), and in other species (Ma et al 2016b;Pandey et al 2018). Asano et al (2008) observed two types of prickles in the cultivated rose 'Laura', described as large size and small size prickles.…”
Section: Two Types Of Prickles Are Present In the Ow Progeny Originamentioning
confidence: 56%
“…We identified two different types of prickles in our population: it appears that GP and NGP originate from glandular and non-glandular structures, respectively. This conclusion is different from previous studies in rose, which reported that prickles were extensions or modifications of glandular trichomes (Kellogg et al 2011), and in other species (Ma et al 2016b;Pandey et al 2018). Asano et al (2008) observed two types of prickles in the cultivated rose 'Laura', described as large size and small size prickles.…”
Section: Two Types Of Prickles Are Present In the Ow Progeny Originamentioning
confidence: 56%
“…Previous studies on raspberry and blackberry prickles have shown that they are outgrowths of epidermal tissue generated from modified glandular trichomes (GTs); once the outermost cells become lignified, lignification continues inward and downwards until the prickles become completely lignified and thus mature [8,9]. A phenotypic analysis of the prickles in Solanum viarum Dunal revealed that they may initiate from GTs or be induced by some signals derived from GTs [10]. Transcriptome analyses in raspberry and S. viarum further identified several transcription factors (TFs) that may play important roles in prickle development [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A phenotypic analysis of the prickles in Solanum viarum Dunal revealed that they may initiate from GTs or be induced by some signals derived from GTs [10]. Transcriptome analyses in raspberry and S. viarum further identified several transcription factors (TFs) that may play important roles in prickle development [10,11]. In eggplant, several quantitative trait loci (QTLs) for prickle have been identified on chromosomes 2, 6, 7 and 8 [3,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In this contest, it is interesting that GTL1 coordinates different genetic elements implicated in various aspects of SA metabolism [147]. Recent data, collected by a differential transcriptomic analysis of epidermis of both prickly and prickleless mutants of Solanum viarum (an important medicinal plant), show that the activity of several defense regulators, such as ethylene, SA, and PATHOGEN RELATED-proteins, is significantly repressed in prickleless mutants [148].…”
Section: Gene and Hormonal Interaction In Trichome Developmentmentioning
confidence: 99%